Development Of Maharah Al-Qira’ah In Arabic Language Learning At Madrasah Aliyah Al-Ma'arif Sungai Duri - Ridwan, Ahmad Ibnu; Alim, Akhmad; Al Kattani, Abdul Hayyie (Yayasan Rahmat Islamiyah, 2024)
The development of Maharah Al-Qira’ah in Arabic Language Learning at MA Al-Ma'arif consists of three parts: First, Planning. Before the learning process is carried out, the teacher first prepares a plan for teaching and learning activities related to teaching materials and methods in the form of a Learning Implementation Plan (RPP), which serves as a teacher's guide in carrying out learning in the classroom. Second, Implementation. In the implementation of Arabic language learning, the learning process does not solely refer to the lesson plan that has been made, but the teacher applies several learning methods or strategies that are in accordance with the level of ability and needs of students such as providing motivation and understanding of the importance of learning Arabic. Third, Evaluation. The evaluation of Arabic learning carried out is evaluating the level of progress and improvement of students' Arabic learning and evaluating the teaching methods or strategies applied by Arabic teachers in the learning implementation process. The Problematics of Arabic Language Learning, a. The problems faced by teachers are the lack of interest and interest in learning Arabic by students, the weak spirit of student learning in the implementation of learning, the lack of student understanding of the importance of learning Arabic, the lack of student Arabic practice in the learning process. b. The problems faced by students are lack of vocabulary mastery, difficulty in pronouncing Arabic, difficulty in memorizing Arabic texts, difficulty in composing sentences using Arabic. Solutions to Overcoming Arabic Learning Problems are Creating a comfortable and effective teaching and learning atmosphere, Providing support and encouragement to students in honing Arabic language skills, Providing understanding and motivation to students regarding the importance of Arabic, Conducting evaluations and practices in the madrasah environment in an effort to improve students' Arabic language skills, Carrying out extra-curricular activities that can add insight and knowledge to students related to Arabic language learning, Updating books in the library related to Arabic language learning materials and methods.